A Case Study of Transitions in Farming and Farm Labor in Southwestern Idaho - Lisa Meierotto; Rebecca L. Som Castellano (Journal of Agriculture, Food Systems, and Community Development, 2019)
Farm labor in the U.S. is undergoing significant transitions. First, fewer farmworkers are migrating in the traditional sense, and more are settling in to rural American communities. Second, more women are working in agriculture—a process referred to as the feminization of agriculture. Third, there has been an increase in so-called “recreational” crops” like marijuana and hops grown for craft microbrew beers. This paper discusses these three transitions in Southwestern Idaho. These transitions were observed during pilot research conducted in Idaho during 2017–2018. We present this paper as a case study of current transitions in American agriculture.